Dampak Dan Resiko Pemindahan Ibu Kota Terhadap Perekonomian Di Indonesia - Delvi Aprillia; Supentri Supentri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
President Jokowi has announced plans to transfer the nation's capital to the Timur Province. This needs to be carefully considered since it has the potential to be risky but can also provide positive effects. The goal of this endeavor is to stabilize Jakarta's position as a hub for business and government that has long been in decline, as well as to lessen economic tensions between the main island of Java and its neighboring islands. This article will analyze the economic climate as well as the risks that the government must address in this particular endeavor. Qualitative research method is a research method that is carried out with a type of descriptive approach The results of the research obtained are the positive impact as well as the risk of the transfer of IKN to Central Kalimantan on the economy in Indonesia. Even if there are potential for PDB growth and inflation that is moderate, there are risks associated with renovation that should be considered, such as working together with the government to mitigate the risk of exceeding budget while building new infrastructure and cities. In addition, there is a potential inflation rate that is higher than expected due to the change in exchange rates, which is attributed to the DPR RI.